Analysis of Learning Problems Bahasa Arab Peminatan for Class XII Students of Religious Programs - Eneng Komariyah Maimun; Hikmah Maulani (Alsuna: Journal of Arabic and English Language, 2022)
Purpose - This study aims to identify and find out the problems of learning Arabic Specialization for class XII in the religious program at one of the public schools in Cianjur Regency and the efforts or solutions to overcome them. Design/methodology/approach - The research method used is descriptive with a qualitative approach. The technique of collecting data is through observation, a questionnaire with six indicators proposed by class XII students of the Religious program. The data analysis technique is by reducing, presenting data and drawing conclusions from existing data Findings/result - Based on the data, it was found that in learning Arabic specialization there were problems faced both in terms of linguistics and non-linguistics that hindered the achievement of learning objectives. Linguistic problems revolve around the internals of Arabic such as the lack of understanding of nahwu sharf. The non-linguistic problems are inhibiting factors that come from outside the language such as student motivation and interest. It is hoped that by knowing this, all components of education can work together to overcome these problems Originality/value - There is a lot of literature that investigates the problems of learning Arabic. However, several studies examine how Arabic is taught and the problems that exist. Thus, this research relates to the problems of learning "Bahasa Arab Peminatan" whose subject weights are different from Arabic in general. Paper type - Research paper